KUALITAS PELAYANAN, HARGA DAN KEPERCAYAAN TERHADAP KEPUTUSAN PENGGUNAAN JASA TRANSPORTASI ONLINE - Siti Maesaroh; Eling Ri Kurniati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The Industrial Revolution 4.0 changes the transportation sector from conventional to digital online transportation, there are pros and cons related to the application of online motorcycle taxi transportation which is considered detrimental to base motorcycle taxis, this study aims to determine the effect of service quality, price and trust on the decision to use online transportation services in Purwokerto. This research uses quantitative research, while the type or type of associative research. The sample used in this method is to use a random sample. Data collection was carried out by means of a questionnaire distributed directly to users of Go-Jek transportation services as many as 131 questionnaires. The data analysis in this study used multiple linear regression analysis with SPSS. The results of this research indicate that service quality, price and trust influence the decision to use and collectively the variables of service quality, price and trust influence the decision to use.